The Urgency of Voluntary Probation and Parole Officer in Criminal Justice System in Indonesia - Saefudin, Wahyu; Nasirudin, Nasirudin; Darmalingganawati, Darmalingganawati (Polteknik Ilmu Pemasyarakatan, 2023)
The role of Probation Officers in the criminal justice system in Indonesia has become increasingly significant following the enactment of Law No. 11/2012 concerning the Juvenile Justice System Law, particularly in terms of guidance and supervision closely correlated with the success rate in the reintegration process of former inmates. However, based on the Prison Database System, the number of PKs in Indonesia still needs to be ideal. The ideal ratio of Probation Officers to clients handled is 9,975, but as of November 2023, only 2,851 Probation Officers positions have been filled, resulting in a deficit of 7,124 officers. This research aims to understand the urgency of appointing voluntary probation officers, analyze the practices of voluntary probation officers in other countries, and project the mechanisms for criteria, appointment procedures, task implementation, and working relationships of voluntary probation officers. The method employed is a literature review involving collecting, evaluating, and synthesizing existing knowledge from various written sources to support or provide a basis for the ongoing research. This research indicates that forming voluntary Probation Officers is an alternative solution to meet staffing needs. Additionally, the establishment of the position of voluntary Probation Officer aligns with Government Regulation No. 31/1999 regarding the Development and Guidance of Inmates, which outlines the procedures and requirements for the establishment of voluntary Probation Officers. In practice, voluntary Probation Officers, also known globally as Volunteer Probation Officers (VPO), in Japan have been deemed successful due to their financial efficiency and service effectiveness. In conclusion, establishing voluntary Probation Officers is an alternative solution that the Ministry of Law and Human Rights should promptly realize. Moreover, the successful practices of voluntary probation officers in various countries, including Japan, can guide the design of policies that encompass criteria, procedures, rights, and responsibilities.